Optimizing 3D printing prosthesis technology for rehabilitation of oral cancer patients - N. Gopi Chander; Lakshita Sharma; Amrutha Manoj Kumar; Lakshmi Raj (Oral Oncology Reports)
Oral cancer patients face significant challenges in prosthetic rehabilitation due to tissue loss from surgical interventions and the lasting side effects of treatments such as radiation therapy. Traditional methods of prosthesis fabrication often struggle to account for the anatomical changes caused by cancer treatments, leading to functional and aesthetic limitations. 3D printing technology, with its ability to produce customized, patient-specific prostheses, presents a promising solution for overcoming these challenges. By employing advanced imaging techniques like CT and MRI, 3D printing allows for the precise modeling of the oral cavity, improving the fit, comfort, and functionality of prostheses.In addition to enhancing the accuracy of prosthesis design, 3D printing plays a crucial role in surgical reconstruction by enabling surgeons to plan more precise interventions. This reduces the need for multiple surgeries and improves recovery time. The integration of 3D printing with oncologic care, including collaboration between surgical teams and oncologists, further streamlines treatment and enhances patient outcomes. Despite these advantages, limitations remain, particularly regarding the durability and biocompatibility of 3D printing materials. Future advancements, including bioprinting and the development of smart materials, hold the potential to further revolutionize prosthetic rehabilitation for oral cancer patients.